PENERAPAN PEDOMAN PENULISAN ILMIAH SEBAGAI UPAYA PENINGKATAN MUTU AKADEMIK DI PERGURUAN TINGGI - Anjar Sulistyani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the urgency of implementing academic writing guidelines as an effort to improve academic quality in higher education institutions. The method used is a literature review by analyzing various thesis writing guidelines, scientific articles, and relevant research methodology books. The findings indicate that academic writing guidelines play a significant role in establishing a quality and integrity-based academic culture. Consistent implementation of guidelines can help students understand the correct structure of scientific papers, encourage the use of valid references, and prevent plagiarism. Compliance with writing guidelines contributes to improving research quality, critical thinking skills, and students’ analytical abilities. Higher education institutions that strictly enforce academic writing guidelines tend to produce graduates with higher competitiveness and stronger academic reputations. The success of implementing academic writing guidelines depends not only on the existence of the guidelines but also on the support of academic supervisors, institutional policies, and the availability of supporting facilities. Therefore, collective commitment, academic writing training, and continuous evaluation are required to ensure that the application of these guidelines enhances the quality of scientific works and strengthens the academic reputation of higher education institutions. Keywords: guideline, academic writing, higher education;